Haematinic Effect Of Hygrophila Spinosa On Induced Anaemic Rats (Applied Biological Research, 2013)
The present study was conducted to assess the haematinic property of Hygrophila  spinosa extract in induced anaemic albino rats with phenylhydrazine. The  haematinic activity of orally administered H. spinosa extract (pre-flowering extract  @ 40 mg kg-1 body weight) and powdered aerial part (@ 40 mg extract kg-1 body weight) was assessed by treating the induced anaemic rats for 30 days. Treatments  ameliorate the anaemic condition by improving haematological parameters and  RBC indices. On 30th day post-treatment, the rats treated with plant extract  showed more improvement in anaemic condition and increase in body weight in  comparison to the rats treated with crude leaf.
Keywords: Anaemia; haematinic; Hygrophila spinosa; pre-flowering extract